LONG-TERM TRENDS IN THE GLOBAL ECONOMY: DEVELOPMENT PROSPECTS IN THE CONTEXT OF GLOBALIZATION AND TECHNOLOGICAL CHANGE - Artikov Zokir Sayfiddinovich; Jamilov Firdavs Otabek o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we explore the long-term changes shaping global disasters as analysts predict developments in the face of globalization and technological change. We begin by discussing the historical context of globalization and the technological advances that shape its structure and growth patterns. This article delves into current trends, examining how globalization and technological change continue to evolve industries, labor markets, and trade dynamics. By summarizing historical perspectives and present analysis, this article offers insight into the evolving landscape of the global economy and suggests potential strategies for future governance developments.